Water quality and communities associated with macrophytes in a shallow water-supply reservoir on an aquaculture farm - Sipaúba-Tavares, Lúcia Helena [UNESP]; Dias, Samuel Generoso [UNESP] (Int Inst Ecology, 2014)
Plankton communities and macrofauna associated to aquatic macrophyte stands in a shallow water-supply reservoir (21 degrees 14'09"S; 48 degrees 18'38"W) on an aquaculture farm were compared to evaluate the relationship between organism densities and some abiotic features of the reservoir. Water and communities associated were sampled at two sites, one in an area with the predominance of Eichhornia azurea (Sw.) Kunth and the other with the predominance of Salvinia auriculata Aublet. Communities associated with macrophytes were sampled with floating quadrants (0.5 m(2)); the macrophytes were washed and plankton and macrofauna were fixated with 4% formalin and 1% lugol iodine; the specimens were then identified and counted. Plankton and macrofauna communities associated with S. auriculata and E. azurea had a similar diversity of species but different (p<0.05) in the abundance of associated organisms. Eichhornia azurea had the highest contents in dry and wet weight, total phosphorus, total nitrogen and organic matter. Planktonic algae were directly correlated with biomass of E. azurea. The taxa with highest densities were Rotifera and Zygnematophyceae. Results showed that the environmental variables associated with macrophytes presence in the shallow reservoir is a strong predictor of favourable conditions to maintain great diversity plankton community and macrofauna associated with plants. The role of macrophytes is important for not only stabilising the clear-water state and maintaining high diversity of organisms associated, but also it seems to be a good alternative to maintaining desirable water-supply quality for aquaculture farms.

Este estudo objetivou comparar a composição da comunidade planctônica e a macrofauna associada aos bancos de macrófitas aquáticas em um reservatório (21º14’09”S e 48º18’38”O) de abastecimento de água para um sistema de aquicultura, avaliando a relação entre a densidade dos organismos e alguns fatores abióticos da coluna d’água. As amostras de água e comunidades associadas foram coletadas em dois locais, um em área dominada por Eichhornia azurea (Sw.) Kunth e outro em área dominada por Salvinia auriculata Aublet. As comunidades associadas com as macrófitas foram amostradas utilizando o método do quadrante (0,5 m2 ), posteriormente lavadas e fixadas com formalina a 4% e lugol a 1%; depois os indivíduos foram identificados e contados. A comunidade planctônica e macrofauna associadas à S. auriculata e E. azurea apresentaram similar diversidade de espécies e, diferiram (p<0,05) em abundância em relação aos organismos associados. Massa seca e fresca, matéria orgânica, fósforo total e nitrogênio total foram mais elevados no tecido vegetal de E. azurea do que em S. auriculata. As algas planctônicas foram correlacionadas diretamente com a biomassa de E. azurea. Os grupos que apresentaram as maiores densidades de espécies foram Rotifera e Zygnematophyceae. Os resultados mostraram que as variáveis ambientais associados à presença de macrófitas em reservatório raso apresentam condições favoráveis na manutenção de grande diversidade da comunidade planctônica e macrofauna associada às plantas. O papel das macrófitas não está ligado somente em manter uma água clara com elevada diversidade de organismos associados, mas também parece ser uma boa alternativa a ser adotada na manutenção da qualidade de água para abastecimento em fazenda de aquicultura.
Qualidade da água e comunidades associadas com macrófitas em um reservatório de abastecimento de água para uma fazenda de aquicultura
Keywords: Floating macrophytes; Plankton; Aquaculture; Water-supply; Macrofauna; Macrófitas flutuantes; Plâncton; Aquicultura; Abastecimento de água; Macrofauna